Acute respiratory infections in children Infecções respiratórias agudas em crianças - Charles Anthony Hart; Luis E. Cuevas (Instituto Materno Infantil de Pernambuco, 2007)
Acute respiratory infections (ARI) are the leading cause of mortality in children under five years of age worldwide and most of these deaths are due to bronchiolitis and pneumonia. Recent evidence from studies using genome detection systems such as polymerase chain reaction or micro-array technology show that, in most cases, these deaths are caused or precipitated by viruses. In this paper, the definitions of upper and lower respiratory tract infections are reviewed. The principal signs of disease severity and the burden of viruses as causes of ARI are described. The prominent role of Respiratory Syncytial Virus is stressed, with data from epidemiological and clinical studies. Other important viral pathogens, such as Human Metapneumovirus, Human coronaviruses and Influenza are examined. The role of newly described viruses, such as bocavirus, is also discussed. The impact of HIV/AIDS in ARI burden and presentation assessed and the weight of Pneumocystis jiroveci and Mycobacterium tuberculosis infections is recognized. It is concluded that there is an urgent need to improve diagnostics, therapeutics and vaccines, as well as macro and micronutrient intake of children of the world, particularly in developing countries. As infecções respiratórias agudas (IRA) são as principais causas da40 mortalidade mundial em crianças menores de cinco anos de idade e a maioria dessas mortes são próprias da bronquiolite e pneumonia. Recentes evidências de estudos usando sistemas de detecção no genoma tais como reação em cadeia da polimerase ou tecnologia de microarrays mostram que, na maioria dos casos, essas mortes são causadas ou precipitadas por vírus. Neste artigo, as definições das infecções dos tratos respiratórios superior e inferior são revisadas. Os principais sinais da gravidade da doença e a carga viral como causas da IRA estão descritas. O papel proeminente do vírus sincicial respiratório é enfatizado, com dados de estudos clínicos e epidemiológicos. Outros importantes patógenos virais, tais como o metapneumovírus humano, o coronavírus humano e influenza são examinados. O papel dos vírus recentemente descritos tais como o bocavírus, é também discutido. O impacto do HIV/AIDS na apresentação e ônus da IRA é avaliado e a sobrecarga das infecções de Pneumocystis jiroveci e Mycobacterium tuberculosis é reconhecidas. Conclui-se que há uma necessidade urgente de melhorar o diagnóstico, a terapêutica e as vacinas, bem como a ingestão de macro e micronutrientes das crianças do mundo, particularmente aquelas de países em desenvolvimento.